Analysis of the phenomenon of corrosion in structural steels from the point of view of their use in industry of civil engineering (Revista de Diavulgación L'esprit Ingénieux, 2021)
on the earth’s crust and which to be transformed through an alloy with the carbon form the material that we know commonly referred to as the steel. There are numerous ways to identifyand classify this type of material depending on its use, whether domestic, industrial or for civil construction. Despite the fact that the steel that has had use in civil engineering is the carbon steel, today have arisen techniques of transformation of this material that have been converted and have made it possible to enhance all of its properties, both physical and mechanical properties. In this research, an analysis was made, relating to the three most common types of steel and used for the manufacture of metal structures (carbon steel, stainless steel and weathering steel), referring mainly to the last two given their degree of usage bothin industry and commerce as in civil engineering and an emphasis on the phenomenon of corrosion. It was determined how to affect their corrosion rates, their properties, and characteristics, all this considering the information obtained through a review of the literature on experimental processes, tests, and laboratory tests. Analyzing corrosion between the different types of steel mentioned, there was a noticeable difference between the effect that causes this injury and the factors that predominate in it, it’s of vital importance to take account of this aspect as it defines the quality of the material at the moment of being used as raw pima especially in the field of engineering in the design of steel structures (especially bridges) given all environmental factors - atmospheric pollutants, social and economic influence your life. Technology is advancing very fast and in the field of civil engineering design of steel structures is becoming a more simplified, definitely steel is a material that has many features, including flexibility, low cost, easy installation that function as advantages over other materials such as concrete.
Keywords: Weathering steel; stainless steel; corrosion; atmospheric corrosion; iron; oxidation; pathology